Is primary hyperparathyroidism a pathogenic factor in some conditions mediated by B lymphocytes hyperactivity? (2013)
Several clinical cases have shown the association of primary hyperparathyroidism and immune conditions related to B-cell hyperactivity. In some of these cases the treatment of hyperparathyroidism led to the resolution of the autoimmune phenomena. Thus, this paper hypothesizes that high levels of parathyroid hormone (PTH) may modify B lymphocytes function and induce the development of autoimmunity mediated by B-cell hyperactivity.